ADVANCE Scholar Program: enhancing minoritized scholars' professional visibility. Issue 3 (26th February 2019) - Carter-Sowell, Adrienne R.; Vaid, Jyotsna; Stanley, Christine A.; Petitt, Becky; Battle, Jericka S.
Abstract : Purpose: The purpose of this paper is to describe a mentoring program developed at a large predominantly white research university that was aimed at retaining and advancing women faculty of color. The ADVANCE Scholar Program pairs each scholar for two years with a senior faculty member at the university who serves as an internal advocate, and with an eminent scholar outside the university who helps the scholar gain prominence in their discipline. Design/methodology/approach: This paper offers a case study of the ADVANCE Scholar Program. The authors describe the intersectional approach to organizational change in this conceptual framework and provide a brief overview of the institution and precursors to the development of the Scholar program. The authors describe the program itself, its rationale, structure and participants in the program. Findings: Overall, the program generated a positive reception and outcomes, and the authors suggest that such a program has the potential to make a positive difference in making the university a more supportive place for a diverse professoriate and recommend it as a model for adoption at other predominantly white research universities. Practical implications: By publishing the operations and the outcomes of this faculty mentoring program, we expect to contribute broadly to a more supportive campus climate for a diverse professoriate. We have developed, implemented, and continue to study this successful model to retain minoritized faculty scholars in the professoriate. Social implications: Women faculty of color are often assigned to serve on committees to meet diversity objectives of the institution and are sought after by students of color from across the university, but this service is not considered. This program, the ADVANCE Scholar Program, pairs each scholar with a senior faculty member who serves as an internal advocate, and an external eminent scholar who guides the scholar in gaining national prominence. These efforts to retain and promote minoritized faculty scholars, altogether, have important implications on the pervasive issues affecting many members of academic communities at the individual, interpersonal and the institutional levels. Originality/value: This case study provides an innovative strategy to tackle the lack of role models and the experiences of social isolation that occurs for women faculty of color with multiply marginalized status. Hence, women faculty of color benefit from a valuable, institutionally supported, university-wide mentoring program designed to increase diversity of minoritized faculty in the professoriate ranks.